A SYSTEMIC FUNCTIONAL LINGUISTICS (SFL) ANALYSIS OF EXPOSITION TEXT AS TEACHING MATERIAL WRITTEN BY PRE-SERVICE TEACHER - Dewi, R. Winda Herdisa (2016)
The research is entitled A Systemic Functional Linguistics (SFL) Analysis of Exposition Text as Teaching Material Written by Pre-Service Teacher. This research aims at observing the teachers' Subject Matter Knowledge competence by analyzing the coherence of analytical exposition texts written by three English pre-service teachers in a senior high school in terms of their schematic structure and theme system. To accomplish this aim, a qualitative research study design involving text analysis and interviews was conducted. It is found out that the pre-service teachers were able to make coherent text seen from Theme and Thematic Progression. Meanwhile, the results from interviews showed that they encountered the challenges. The challenges were to make the text more relevant and coherent and to distinguish between censorship and professional. From the analysis of interview, nonetheless the texts written by pre-service teachers seemed to generally reflect a sense of accomplishment from the professional categories point of view.;--- Penelitian ini berjudul A Systemic Functional Linguistics (SFL) Analysis of Exposition Text as Teaching Material Written by Pre-Service Teacher. Penelitian ini bertujuan mengamati Subject Matter Knowledge seorang guru dengan menganalisis koherensi teks eksposisi analitis yang ditulis oleh tiga guru PPL bahasa Inggris di SMA dalam hal struktur skema dan sistem tema. Untuk mencapai tujuan ini, desain penelitian kualitatif yang melibatkan analisis teks dan wawancara dilakukan. Penelitian menemukan bahwa guru PPL mampu membuat teks yang koheren dilihat dari tema dan sktuktur skema. Sementara itu, hasil dari wawancara ditemukan bahwa mereka menghadapi tantangan. Tantangannya adalah membuat teks lebih relevan dan koheren dan untuk membedakan antara sensor dan profesional. Dari hasil analisis wawancara, ditemukan bahwa teks-teks yang ditulis oleh guru PPL mencerminkan pencapaian dari sudut pandang kategori profesional prestasi dari titik kategori profesional pandang.